The Cambridge companion to Shostakovich - Fairclough, Pauline, 1970-; Fanning, David J., 1955- (New York : Cambridge University Press, 2008)
As the Soviet Union's foremost composer, Shostakovich's status in the West has always been problematic. Regarded by some as a collaborator, and by others as a symbol of moral resistance, both he and his music met with approval and condemnation in equal measure. The demise of the Communist state has, if anything, been accompanied by a bolstering of his reputation, but critical engagement with his multi-faceted achievements has been patchy. This Companion offers a new starting point and a guide for readers who seek a fuller understanding of Shostakovich's place in the history of music. Bringing together an international team of scholars, the book brings up-to-date research to bear on the full range of Shostakovich's musical output, addressing scholars, students and all those interested in this complex, iconic figure.
Instrumental works. Personal integrity and public service : the voice of the symphonist / Eric Roseberry ; The string quartets : in dialogue with form and tradition / Judy Kuhn ; Paths to the First symphony / David Fanning ; Shostakovich's Second piano sonata : a composition recital in three styles / David Haas ; I took a simple little theme and developed it : Shostakovich's string concertos and sonatas / Malcolm MacDonald -- Music for stage and screen. Shostakovich and the theatre / Gerard McBurney ; Shostakovich as opera composer / Rosamund Bartlett ; Shostakovich's ballets / Marina Ilichova ; Screen dramas : Shostakovich's cinema career / John Riley -- Vocal and choral works. Between reality and transcendence : Shostakovich's songs / Francis Maes -- Slava! shostakovich's 'official compositions' / Pauline Fairclough -- Performance, theory, reception. A political football : Shostakovich reception in Germany / Erik Levi -- The rough guide to shostakovich's harmonic language / David Haas ; Shostakovich on record / David Fanning ; Jewish existential irony as musical ethos in the music of Shostakovich / Esti Sheinberg.
Includes bibliographical references (p. ) and index.
Keywords: Shostakovich, Dmitriĭ Dmitrievich, -- 1906-1975.; Shostakovich, Dmitriĭ Dmitrievich, -- 1906-1975 -- Criticism and interpretation